2013
DOI: 10.4085/1062-6050-48.2.11
|View full text |Cite
|
Sign up to set email alerts
|

Test-Retest and Interrater Reliability of the Functional Movement Screen

Abstract: Context: The Functional Movement Screen (FMS) is a popular test to evaluate the degree of painful, dysfunctional, and asymmetric movement patterns. Despite great interest in the FMS, test-retest reliability data have not been published.Objective: To assess the test-retest and interrater reliability of the FMS and to compare the scoring by 1 rater during a live session and the same session on video.Design: Cross-sectional study. Setting: Human performance laboratory in the sports medicine center.Patients or Oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(101 citation statements)
references
References 10 publications
7
94
0
Order By: Relevance
“…The reliability of composite FMS scores were consistent with the findings of previous studies, with the 6 raters demonstrating an excellent level of agreement overall (ICC 0.91; 95% CI 0.81-0.96) [6][7][8][9]. However, as composite data sets were found to be not normally distributed the possibility of ICC inflation cannot be overlooked [16].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The reliability of composite FMS scores were consistent with the findings of previous studies, with the 6 raters demonstrating an excellent level of agreement overall (ICC 0.91; 95% CI 0.81-0.96) [6][7][8][9]. However, as composite data sets were found to be not normally distributed the possibility of ICC inflation cannot be overlooked [16].…”
Section: Discussionsupporting
confidence: 80%
“…The intra-rater reliability of the FMS has been investigated with conflicting results; particularly when groups of raters with varying FMS experience have been compared [5][6][7][8][9]. This could however be related to the observed methodological heterogeneity within the current evidence base [10].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the finding of this study indicated that right in-line lunge task had the minimum reliability and right active leg raise task, the maximum reliability. This result is consistent with previous studies [23]. Onate and Dewey reported that right leg raise test had the lowest inter-rater reliability [22] whereas this task in the present study showed 100% agreement.…”
Section: Discussionsupporting
confidence: 82%
“…trunk stability pushup movement pattern, and rotary stability movement pattern. FMS had a good intra-rater reliability (ICC=0.6) [13].…”
Section: Functional Movement Screenmentioning
confidence: 99%